Indigenous people and Geographic Information Systems for micro level forest management: a case study in Parambikulam Wildlife Sanctuary - Sekhar Lukose Kuriakose and P. Pugazhendi (Journal of Conservation Planning Vol 1 (2005) 74-85, 2005)
Parambikulam Wildlife Sanctuary, located in the oblivions of Anamalai hills, in Palakkad district of Kerala is highly traversed by streams of the upper reaches of Chalakkudy River. Major part of the sanctuary becomes dry for a period from December to May. An inventory of the seasonal character of individual stream segments across a year canact as a knowledge source for forest administrators in effective habitat management planning. It is also equally important to know the distribution of critical species in the sanctuary. The paper describes three separate attempts, all part of the 10 year management plan preparation process carried out from the year 2001 to 2002 where in inputs from and efforts of indigenous people were used in preparing a forest management planning database; first, it describes how indigenous people and their knowledge on the seasonality of the streams were collected and compiled into a GIS, second, how these communities helped in collecting information and mapping tiger distribution in the sanctuary and third how the assistance from indigenous people were utilized in collecting soil samples for a scientific analysis. Such attemptsincorporating indigenous communities in scientific forest management planning will bridge the gap between bureaucracy and local communities, thereby resulting in a harmonious forest management scenario. Further, these datasets can act as inputs in scientific models that require input parameters related to the seasonality of streams, for example, mapping zones of varying soil moisture and erosion, as it was the case with the present study. Present study was the humble attempt of a geographer and a forest administrator in utilizing indigenous people and their local knowledge as data sources in GIS for effective forest management. The attempt resulted in a detailed GIS database containing the seasonality of the streams and also in deriving a generalized map of the distribution of tigers in the sanctuary